2017
DOI: 10.1007/s12098-016-2280-2
|View full text |Cite
|
Sign up to set email alerts
|

Heated Humidified High-Flow Nasal Cannula for Prevention of Extubation Failure in Preterm Infants

Abstract: In the index study, the extubation failure rate was not statistically different between infants who were on HHHFNC or CPAP support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…In contrast to studies of HFNC as postextubation support , Roberts et al found HFNC as primary support to be not only inferior to nCPAP, but the difference was obvious prior to full recruitment, and was significant in both the intention‐to‐treat and per‐protocol analyses. The authors posit the higher rate of treatment failure in the HFNC group ‘may reflect its reduced effectiveness in infants with surfactant‐deficient lungs’.…”
mentioning
confidence: 80%
“…In contrast to studies of HFNC as postextubation support , Roberts et al found HFNC as primary support to be not only inferior to nCPAP, but the difference was obvious prior to full recruitment, and was significant in both the intention‐to‐treat and per‐protocol analyses. The authors posit the higher rate of treatment failure in the HFNC group ‘may reflect its reduced effectiveness in infants with surfactant‐deficient lungs’.…”
mentioning
confidence: 80%
“…randomised 161 preterm infants <32 weeks' GA and found no difference in these outcomes overall, but treatment failure was higher with nHF in the smaller infants (26–28 +6 weeks' GA). A second, smaller study found a higher rate of treatment failure but a similar rate of intubation in infants <32 weeks' GA managed with nHF; the intubation rates were similar due to the use of rescue CPAP in the nHF arm.…”
Section: Indications For Nhf Therapymentioning
confidence: 91%
“…In the past, endotracheal intubation was the main respiratory support in preterm infants, but prolonged intubation can increase risks of infection, lung injury, and chronic lung disease. Therefore, the strategy has been shifted to initiate non-invasive respiratory support as soon as possible to minimize duration of mechanical ventilator [7].…”
Section: Pretermmentioning
confidence: 99%